Pengembangan Sistem Terdistribusi Pemantauan Data Untuk Meningkatkan Kunjungan Mahasiswa di Perpustakaan - Armandito; Hetty Rohayani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A library is a work unit of a particular agency or institution that manages library materials, both in the form of books and non-books, which are managed systematically according to regulations so that they can be used as a source of information. Nowadays, libraries are often considered old-fashioned, thereby reducing public interest, especially students, because they are considered old-fashioned and stiff. Therefore, I wrote this article to help overcome and attract students at Muhammadiyah University of Jambi so that they can help the library increase the number of visits. This system was created with the aim of displaying an attractive login, displaying student attendance ranking data to attract interest and appeal to other students and also making it easier for students to obtain their data without having to bother asking the library. This was created using the Distributed System method with the result of increasing the number of student visits to the Jambi Muhammadiyah University Library.